Fistula Aorta - Atrium Kanan - Harun, Andi L A; Attamimi, Luthfi; Latief, Nikmatia; Asriyani, Sri (UNIVERSITAS SAM RATULANGI, 2021)
Abstract: Aortic - right atrial fistula is a channel of blood vessels originating from one of the valsalva sinuses and ending in the superior vena cava or right atrium. This fistula is an abnormal vascular connection that causes blood flow from the high-resistance aortic circuit to the low-resistance right atrium. We report a case of a 34-year-old male patient diagnosed with aortic - right atrial fistula with clinical manifestations of spasms since 1 month. The incidence of aortic - right atrial fistula is most common between the ages of 9 and 45 years. The cause of this condition appears to be an inherited deficiency / weakness of the elastic lamina in the aortic medium. Right aorto-atrial fistula has varied clinical manifestations such as acute pulmonary edema, chronic heart failure and can also be found incidentally. Cardiac MSCT with contrast shows the results of the aorta to right atrial fistula. This patient was treated with furosemide and aspilet treatment.Key words: Aortic - right atrial fistula, MSCT cardiac.Â Â Abstrak: Fistula aorta - atrium kanan adalah celah atau saluran pembuluh darah yang berasal dari salah satu sinus valsava dan berakhir di vena cava superior atau atrium kanan. Fistula ini merupakan koneksi vaskular abnormal yang menyebabkan aliran darah dari sirkuit aorta dengan resistensi tinggi ke atrium kanan dengan resistansi rendah. Kami melaporkan kasus pasien laki-laki berusia 34 tahun dengan diagnosis fistula aorta - atrium kanan dengan manifestasi klinis sesak sejak 1 bulan. Insiden fistula aorta - atrium kanan tersering pada usia antara 9 â€“ 45 tahun. Penyebab kondisi ini tampaknya merupakan defisiensi / kelemahan bawaan lamina elastis di media aorta. Fistula aorto-atrium kanan memiliki manifestasi klinis bervariasi seperti edema paru akut, gagal jantung kronis dan dapat pula ditemukan secara insidental. Pada pemeriksaan MSCT cardiac dengan kontras mendapatkan hasil gambaran aorta to right atrial fistula. Pasien ini ditatalaksana dengan diberikan pengobatan furosemide dan aspilet.Kata kunci: Fistula aorta - atrium kanan, MSCT cardiac.